Italo Calvino and the Compass of Literature - Bolongaro, Eugenio, 1959- (Book collections on Project MUSE., 2003)
Looking at five of Italo Calvino's often neglected early novels: The Young People of Po, The Cloven Viscount, The Baron in the Trees, The Non-Existent Knight, and The Watcher, Eugenio Bolongaro argues that these works, written between 1948 and 1963, contain a sustained meditation on the role of the intellectual and on the irreducible ethical and political dimension of literature. This meditation provides an insight into a crucial moment in Calvino's development as a writer, and allows Bolongaro to lay the groundwork for a more 'political' reading of Calvino's later work. Italo Calvino and the Compass of Literature firmly situates Calvino within his historical context the cultural revival of post-World War II Italy by relating these early novels to Calvino's political and critical writings which played an important role in the cultural debates of the time. This approach provides a key to understanding Calvino's work in a new light, ably demonstrating that Calvino's full literary significance cannot be understood in isolation from the politics and cultural movements of the period. One of the few book-length English-language works on Calvino's early writings, Italo Calvino and the Compass of Literatur will prove to be an indispensable tool to Italianists and literary studies scholars.